Biografi Ida Bagus Raka Pudjana sebagai Refleksi Sejarah Drama Gong di Bali 1960-an –1990-an - Sri Lestari (Universitas Udayana, 2023)
The history of Balinese drama gong art is rarely written, and so is the biography of its artists. The purpose of this article is twofold: to describe the biography of a Balinese drama gong artist, Ida Bagus Raka Pudjana, and to describe the life of Balinese drama gong from the 1960s to the 1990s. The focus is on tracing the history of drama gong through the figure of Raka Pudjana, an artist with the stage name Komang Apel (Mr Chubby) who was very famous in his time. Research data were collected through interviews, archival studies, and document reviews related to the existence of drama gong and the figure of Ida Bagus Raka Pudjana. The collected data was analyzed using Bourdieu's generative structuralism theory. This study concludes that Raka Pudjana's popularity as a drama artist was mostly obtained from his long-standing practice of playing drama from the community level to various cities throughout Bali. The cultural capital obtained from playing drama gong also contributed to the flourishing of drama gong that he was belong to. This study is expected to provide a model for writing biographies or histories of Balinese performing arts that have many maestros.